Tindakan Plagiarisme Pada Dunia Pendidikan Studi Litratur LKP Palcomtech Baturaja - Rosita Diana; Edi Surya Negara (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2021)
The rampant phenomenon of plagiarism in the academic world is categorized as a violation due to the act of appropriating the work of others. Engaging in plagiarism hampers students' development of creative and critical thinking patterns, leading them to seek convenience, resulting in intellectual impoverishment for future generations. This research aims to explore the meaning of plagiarism for students and the motives behind students engaging in plagiarism within the university context. Additionally, the study aims to outline the various forms of plagiarism committed by student. The research employs a qualitative method, utilizing Alfred Schutz's phenomenological approach, which categorizes human consciousness into two aspects: because of motive (reasons for actions) and in order to motive (goals of actions). Data collection techniques involve observation and interviews, while data analysis follows Miles and Huberman's techniques, including data reduction, presentation, and exposition. The findings reveal that students engage in plagiarism for various reasons, such as the teaching culture of instructors, easy access to information, lack of knowledge about plagiarism, insufficient supervision, orientation towards grades and GPA, and economic factors.